A cost estimating framework for electronic, electrical and electromechanical (EEE) components obsolescence within the use-oriented product-service systems contracts - Romero Rojo, Francisco Javier; Roy, Rajkumar; Shehab, Essam; Cheruvu, Kalyan; Mason, Phil (Professional Engineering Publishing, 2012)
This paper provides a cost estimating framework for electrical, electronic and electromechanical (EEE) components obsolescence, which represents the main source of obsolescence issues, owing to the increasingly short life cycle of these types of component. The framework comprises several areas: component complexity levels, obsolescence management levels, obsolescence resolution profiles and obsolescence cost metrics. Several studies, based on the literature and on interaction with numerous obsolescence management experts from industry, have been employed in this research, following a systematic approach. The framework is able to estimate the non-recurring cost of obsolescence during the contracted period within the inservice phase. This is based on the information available at the bidding stage concerning the product breakdown structure (PBS) and the obsolescence management strategy deployed. This framework has been validated at four different UK organizations in the defence and aerospace sectors using seven case studies, one of which is presented in this paper in detail.